Second-Trimester Diagnosis of Triploidy: A Series of Four Cases - J. B. Wick; K. J. Johnson; J. O'Brien; M. J. Wick (Thieme Medical Publishers, Inc., 2013)
Abstract Triploidy occurs in 2 to 3% of conceptuses and accounts for approximately 20% of chromosomally abnormal first-trimester miscarriages. As such, triploidy is estimated to occur in 1 of 3,500 pregnancies at 12 weeks', 1 in 30,000 at 16 weeks', and 1 in 250,000 at 20 weeks' gestation. We present a series of four cases of second-trimester triploidy diagnosed at our center within a 1-year timeframe. This is remarkable, as the delivery volume at our institution is roughly 2,500/y. All patients were at least 19 weeks' gestation, with multiple abnormalities identified on prenatal ultrasound at 18 to 20 weeks' gestation; all fetuses had lethal anomalies, but anomalies were not consistent between cases. All patients elected for induction of labor before 24 weeks' gestational age. Two of the four cases had amniocentesis and chromosome analysis prior to delivery, and two cases had chromosome analysis performed on fetal tissue after delivery. All fetuses were examined following delivery. This case series demonstrates that the diagnosis of triploidy may not be obvious based on ultrasound and physical examination findings and highlights the importance of routine chromosome analysis on all prenatal diagnoses of multiple congenital anomalies prior to consideration of more complex genetic testing.